The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1021/ja961847r
|View full text |Cite
|
Sign up to set email alerts
|

An Energetically Feasible Mechanism for the Activation of the C−H Bond by the 16-Electron CpM(PH3)(CH3)+ (M = Rh, Ir) Complex. A Theoretical Study

Abstract: The reaction mechanism for the activation of C−H bonds by coordinatively unsaturated CpM(PH3)(CH3)+ (Cp = cyclopentadienyl; M = Rh, Ir) has been investigated by ab initio molecular orbital methods. Of the two possible mechanisms, an oxidative addition−reductive elimination process (path 1) and a σ-bond metathesis mechanism through a four-center transition state (path 2), only the former is found for the 16-electron Ir cation, while the Rh case might adopt the latter. The reaction trajectory of path 1 for the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 27 publications
2
67
0
Order By: Relevance
“…3,63-66 Recent reports of Ir(III) systems that activate C-H bonds have prompted speculation on the mechanism of the C-H bond-breaking step of late transition metal systems for which oxidative addition would yield an unusually high formal oxidation state. 41,[67][68][69][70][71][72][73] To assist efforts to discern the C-H activation pathway for catalysis using complex 1, DFT calculations have been employed for benzene C-H activation by the {(Tab)Ru II (CO)(Me)} fragment. Oxidative addition to form the Ru(IV) complex {(Tab)-Ru IV (CO)(Me)(H)(Ph)} (followed by reductive elimination of methane) and a non-oxidative addition reaction with simultaneous C-H bond-breaking and bond-forming have been considered (Scheme 10).…”
Section: Scheme 8 Mechanism For Benzene C-h Activation By (Tab)ru(ncmentioning
confidence: 99%
“…3,63-66 Recent reports of Ir(III) systems that activate C-H bonds have prompted speculation on the mechanism of the C-H bond-breaking step of late transition metal systems for which oxidative addition would yield an unusually high formal oxidation state. 41,[67][68][69][70][71][72][73] To assist efforts to discern the C-H activation pathway for catalysis using complex 1, DFT calculations have been employed for benzene C-H activation by the {(Tab)Ru II (CO)(Me)} fragment. Oxidative addition to form the Ru(IV) complex {(Tab)-Ru IV (CO)(Me)(H)(Ph)} (followed by reductive elimination of methane) and a non-oxidative addition reaction with simultaneous C-H bond-breaking and bond-forming have been considered (Scheme 10).…”
Section: Scheme 8 Mechanism For Benzene C-h Activation By (Tab)ru(ncmentioning
confidence: 99%
“…CH 4 system, [6,7] the Os system goes through a twostep mechanism with the lowest C À H activation barrier; the reaction in the Fe system proceeds by a one-step mechanism with the highest activation barrier, and the Ru system is somewhere in between. In the Ru system, the intermediate and the transition states are structurally and energetically similar.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In these activation reactions, it is believed that the hydrocarbon molecule (HR) is first coordinated to the cationic metal fragments, [Cp*(PMe 3 [Cp(PH 3 )IrMe] favored the oxidative addition/reductive elimination (OA/RE) pathway (a two-step mechanism) with the formation of an intermediate Ir V complex (Scheme 1a). [6,7] Theoretical studies on the CÀH activation mechanisms by analogous complexes [Cp(PH 3 )MCH 3 ] (M Rh and Co) have also been carried out. [8] The results showed that the CÀH activation of methane by [Cp(PH 3 3 ] proceeded via a four-center transition state (a one-step mechanism) with a high activation barrier (Scheme 1b); on the other hand, the reaction seemed to adopt a mechanism somewhere in between the OA/RE and the four-center process with [Cp(PH 3 [9] The proposed activation was later calculated to have much higher reaction barriers relative to the oxidative addition/reductive elimination pathway.…”
mentioning
confidence: 99%
“…1). 12 Further examples of these one-step 'oxidative' reaction steps followed 13 and now it is apparent that SBM is possible at both early and late TM centres. In the following, we shall use the term SBM as a general label for these processes, although, as discussed below, several terms have been proposed by different groups.…”
Section: Introductionmentioning
confidence: 99%